The concept of culture in Cioran's early texts - Pérez, Sergio Andrés (2025)
Analysis of the concept of culture in the first texts of Cioran, published in Spanish for the first time in 2019, written during the end of his university studies and his first life experiences outside of Romania. Criticism of the Enlightened conception of culture and his postmodern becoming; the Romanian philosopher proposes concrete existence, individual, suffering and real life as the only way out against the consequences that modernity has had on the consciousness of the human being and his relationship with the environment. Cioran advocates the acceptance of the irrational, culture as a set of creative stages and vitalism against other cultural schemes, socially imposed, comfortable but limiting and insufficient to answer the fundamental questions of the human being.